2020
DOI: 10.3892/etm.2020.9160
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 regulates sFRP4 expression without affecting the methylation of sFRP4 promoter DNA in colorectal cancer cell lines

Abstract: Abnormal activation of the Wnt signaling pathway is found in 90% of colorectal cancers (CRCs). Secreted frizzled-related protein 4 (sFRP4) serves as an antagonist of the canonical Wnt signaling pathway. Epigenetic alterations, including changes in DNA methylation and histone methylation, may influence the expression of sFRP4. Polycomb group (PcG) proteins are epigenetic transcriptional repressors that selectively repress gene expression by forming polycomb repressive complexes (PRCs). Enhancer of zeste homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As it was proven from previous studies that miR-298 correlates negatively with its target gene polycomb protein enhancer of zeste2 (EZH2) in ovarian cancer 12,49 . As well, the authors identified secreted frizzled-related protein 1 (SFRP1) which is a wnt signaling antagonist as a target gene of EZH2 in rheumatoid arthritis synovial fibroblasts and found that EZH2 silencing results in a significant increase in SFRP1 mRNA 50,51 . Besides wnt signaling inhibition, SFRP overexpression may also cause a marked increase of Th17 cells in RA synovial fluid 40,52 .…”
Section: Discussionmentioning
confidence: 99%
“…As it was proven from previous studies that miR-298 correlates negatively with its target gene polycomb protein enhancer of zeste2 (EZH2) in ovarian cancer 12,49 . As well, the authors identified secreted frizzled-related protein 1 (SFRP1) which is a wnt signaling antagonist as a target gene of EZH2 in rheumatoid arthritis synovial fibroblasts and found that EZH2 silencing results in a significant increase in SFRP1 mRNA 50,51 . Besides wnt signaling inhibition, SFRP overexpression may also cause a marked increase of Th17 cells in RA synovial fluid 40,52 .…”
Section: Discussionmentioning
confidence: 99%
“…They are diagnostic and prognostic biomarkers and suppress the growth and metastasis of CRC tumor cells. SFRP4 and SFRP5 may also inhibit invasion in CRC, but the underlying mechanisms in regulating the signaling pathways are more complex by comparison ( 32 , 33 , 44 ). Additional studies focusing on the SFRPs family as it relates to CRC should be undertaken to clarify their overall role and potentially derive a novel therapeutic regimen.…”
Section: Dna 5mc Methylation: a Robust Prognostic Biomarker In Crcmentioning
confidence: 99%
“…The different regulatory effects on the same protein between the two reveal that CBX7 may be independent of PRC1 composed of BMI-1 to achieve EMT inhibition. Not surprisingly, like CBX7 in breast cancer, abnormal activation of the Wnt signaling pathway is found in 90% of colon cancer, and one of the reasons may be the absence of secreted frizzled-related protein 4(sFRP4) (Liu et al, 2020). The sFRP4 could compete with Wnt proteins via binding their receptor (Frizzled) to act as an antagonist of the Wnt signaling pathway in colonic cancer (Liu et al, 2006;Liu et al, 2020).…”
Section: Colonic Cancermentioning
confidence: 99%
“…Not surprisingly, like CBX7 in breast cancer, abnormal activation of the Wnt signaling pathway is found in 90% of colon cancer, and one of the reasons may be the absence of secreted frizzled-related protein 4(sFRP4) (Liu et al, 2020). The sFRP4 could compete with Wnt proteins via binding their receptor (Frizzled) to act as an antagonist of the Wnt signaling pathway in colonic cancer (Liu et al, 2006;Liu et al, 2020). Interestingly, both DKK-1 and sFRP4 are antagonists of the Wnt signaling pathway, but the effect of CBX7 in regulating sFRP4 in colon cancer is quite different from the effect of regulating DKK-1 in breast cancer.…”
Section: Colonic Cancermentioning
confidence: 99%
See 1 more Smart Citation